Clinical Medical Students’ Experiences of Unprofessional Behaviour and How These Should Inform Approaches to Teaching of Professionalism - Ozotu Rosemary Abu; Sanni O Abu; Gerard Flaherty (MedEdPublish, 2016)
Objectives: